Trees matter: Accounting for silvopastoral systems’ contributions to national GHG inventories - Suber, Marta; Arango, Jacobo; Torres, Carlos Felipe; Rosenstock, Todd S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The integration of trees in pasture lands have significant mitigation potential. However, this potential is currently constrained by logistical and political obstacles.